Vitamin D level and low-energy fracture risk in children and adolescents: a population-based case-control study of 45 cases - Assaf, Elio; Nicolas, Georges; Hoyek, Fadi; Abi Fares, Georges; Lahoud, Jean Claude; Hajj, Rabih; Mohs, Elisabeth; Dally, Franz-J.; Hetjens, Svetlana; Gravius, Sascha; Darwich, Ali (Journal of pediatric orthopaedics, 2024)
The objective of this study is to document the rate of vitamin D deficiency and insufficiency among children with low-energy fractures and compare it to fracture-free control group. We included all children under 15 years presenting to the emergency department with low-energy fractures; controls were children without history of fractures from the outpatient department. Conventional X-ray and laboratory blood tests were performed. Vitamin D deficiency was defined as serum level ≤20 ng/ml, and the mean values were compared through two-sample t-tests. The influence of vitamin D on the fractures was defined using Chi-square test, significance with P-value < 0.05. The relationships between variables and odds of fracture occurrence were examined using logistic regression models. The final sample included 37 cases (30 males, 7 females, 7.4 ± 3.7 years) and 70 control individuals (42 males, 28 females, 7.8 ± 4.6 years) without significant differences regarding age, sex, and month of inclusion. Children with fractures had lower levels of vitamin D (21.87 ± 8.40 ng/ml vs. 25.89 ± 7.62 ng/ml) (P = 0.01). Vitamin D played a protective role against low-energy fractures (OR, 1.08; 95% CI, 1.01-1.14; P = 0.02), boys showed three times greater fracture risk than girls (OR, 3.00; 95% CI, 1.12-8.07; P = 0.03). Finally, vitamin D deficiency correlated with almost five times increased risk of pediatric low-energy fractures (OR, 4.63; 95% CI, 1.92-11.18; P = 0.001). This is the first MENA study establishing a relation between vitamin D deficiency and low-energy fractures among children and adolescents. The findings show the protective role of vitamin D on the pediatric bone and may help physicians preventing morbidity on children and costs on their families and the socioeconomic health system.
Gesehen am 20.02.2025